Use of Slide-Tape and Video Cassettes in County Extension Office Self-Teaching Centers - Mark Eclov; John Pates (Journal of Applied Communications, 1980)
This study was funded as a Special Project by USDA, SEA-Extension, with Ovid Bay as liaison.